Hiking tourism: Motives and behaviours: A case study - Moira Polyxeni; Mylonopoulos Dimitrios; Terzoglou Elli (University Educons, Faculty of Sports and Tourism, Novi Sad, 2021)
Hiking is a physical activity aiming at recreation, training, and physical fitness. As a rule, people are engaged in this activity during vacations. However, very often, hiking is the main motive for travelling. This very fact allows us to refer to hiking as a distinct type of tourism, being the very reason to make a trip. In Greece, both Greeks and foreigners engage in this activity, following one of the two European long-distance footpaths (E4 and E6). This research aims at investigating motives, attitudes and behaviours of Greek hikers, members of the "Friends of Mountain and Sea Club", who undertake hiking tours in Greece and abroad. The research indicates that the main motive the hikers have, are contact with nature, wish to explore new places, and getting to know the civilization of different regions. On the way to their destination, hikers, in addition to hiking, also visit places and monuments of cultural interest. This form of tourism is environment friendly, as the majority of hikers respect and protect the natural and cultural environment.